Вейвлет анализ при обработке данных исследования гидротехнических сооружений - Ковбаса, А.Л. (Моделювання та інформаційні технології, 2010)
In this paper a special approach monitoring data of hydraulic
structures. These benefits approach, as well as shortcomings of the classical method of
data processing for monitoring hydraulic structures. Displaying results of model
experiments.